Infusa bunga rosella (Hibiscus sabdariffa L.)sebagai obat kumur menurunkan jumlah plak pada mahkota akrilik Infusion of roselle flower (Hibiscus sabdariffa L.)as mouthwash decrease plaque on acrylic crown - Edy Machmud; Moh. Dharmautama; Erwin Sutono (Journal of Dentomaxillofacial Science, 2013)
An alternative treatment for extensive dental caries is using jacket crown. But this restoration could accumulate dentalplaque and can lead to gingivitis. Mouthwash is believed could reduce plaque. Nowadays, most of mouthwash inmarket contains alcohol so that not all individuals can use it. For that reason, we need a free of alcohol mouthwash.The use of medicinal plants from natural materials is increasingly widespread and will be a part of life. One type oftraditional medicinal plants are now widely consumed across the world is roselle flower (Hibiscus sabdariffa L.)because it cointains flavonoid that are fungistatic, fungicid, and bacteriostatic. This studywas aimed to determine theeffective concentration of roselle infusion ingredients to reduce the amount of plaque in acrylic crown. Five peopleusing acrylic crown were asked to rinse using 4 concentration of roselle infusion and distilled water as control for 30seconds, with time interval 1 week for each concentration. Examination of the amount of plaque was performed beforeand after rinsing. The results showed that mouthwash made from roselle infusion is able to reduce the amount ofplaque in acrylic crowns (P<0.05). It was concluded that concentration of 20% roselle mouthwash effectively reducingthe number of plaques at acrylic crown.